The protective effect of polarized, incoherent, polychromatic light on white mice infected with influenza A virus - N. A. Mamedaliev; V. A. Divocha (Kazimierz Wielki University, 2017)
Under the influence of polarized light, the reproduction of the influenza A virus in the mice has been slowed. The survival rate of mice infected with a lethal dose of influenza A virus was 50%, compared to the control group.